Subjects, Topics, and Anchoring to the Context. (9th June 2019) - Hinterhölzl, Roland
Abstract: The article discusses the connection between the syntactic and semantic properties of weak, strong, and referential DP subjects. In particular, I argue that nominal expressions possess a situation argument and that their interpretation and their distribution follow from the presuppositional requirements that the determiner imposes on the individual argument and situation argument of its complement nominal. These presuppositional requirements, I then argue, are embodied by local relations of the subject to a distinct head in the C domain, Fin 0 in the system of Rizzi 1997, where specific referential values of discourse antecedents are accessible.